New taxa of Elatostema (Urticaceae) from Thailand and India (Bangladesh Journal of Plant Taxonomy, 2011)
In this study, one new species and one new variety are described and illustrated. Elatostema intanondense Q. Lin (Urticaceae), collected from Doi Intanond of Chiang Mai in Thailand, is morphologically similar to E. subincisum Weddell, but differs by having obscure stipules (vs. conspicuous, linear-lanceolate, 5-6 mm long in E. subincisum), and elliptic to lanceolate nanophylls, 3-7 × 1.5-3.0 mm (vs. absent in E. subincisum). Elatostema ranongense Yahara var. glabroum Q. Lin, a new variety collected from Khasi Hills in Mawhplong of Meghalaya, India. This new variety has glabrous stems and glabrous leaves that differs from var. ranongense that having densely hirtellous stems, densely strigillose leaf blade on abaxial surface along veins.Keywords: Elatostema; E. intanondense; E. ranongense var. glabroum; Urticaceae.DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9300Bangladesh J. Plant Taxon. 18(2): 149-152, 2011 (December)